Lutzomyia longipalpis saliva or salivary protein LJM19 protects against Leishmania braziliensis and the saliva of its vector, Lutzomyia intermedia. - Natalia M Tavares; Robson A Silva; Dirceu J Costa; Maiana A Pitombo; Kiyoshi F Fukutani; José C Miranda; Jesus G Valenzuela; Aldina Barral; Camila I de Oliveira; Manoel Barral-Netto; Claudia Brodskyn (Public Library of Science (PLoS), 2011)
BACKGROUND: Leishmania transmission occurs in the presence of insect saliva. Immunity to Phlebotomus papatasi or Lutzomyia longipalpis saliva or salivary components confers protection against an infection by Leishmania in the presence of the homologous saliva. However, immunization with Lutzomyia intermedia saliva did not protect mice against Leishmania braziliensis plus Lu. intermedia saliva. In the present study, we have studied whether the immunization with Lu. longipalpis saliva or a DNA plasmid coding for LJM19 salivary protein would be protective against L. braziliensis infection in the presence of Lu. intermedia saliva, the natural vector for L. braziliensis. METHODOLOGY/PRINCIPAL FINDINGS: Immunization with Lu. longipalpis saliva or with LJM19 DNA plasmid induced a Delayed-Type Hypersensitivity (DTH) response against Lu. longipalpis as well as against a Lu. intermedia saliva challenge. Immunized and unimmunized control hamsters were then intradermally infected in the ears with L. braziliensis in the presence of Lu. longipalpis or Lu. intermedia saliva. Animals immunized with Lu. longipalpis saliva exhibited smaller lesion sizes as well as reduced disease burdens both at lesion site and in the draining lymph nodes. These alterations were associated with a significant decrease in the expression levels of IL-10 and TGF-β. Animals immunized with LJM19 DNA plasmid presented similar findings in protection and immune response and additionally increased IFN-γ expression. CONCLUSIONS/SIGNIFICANCE: Immunization with Lu. longipalpis saliva or with a DNA plasmid coding LJM19 salivary protein induced protection in hamsters challenged with L. braziliensis plus Lu. intermedia saliva. These findings point out an important role of immune response against saliva components, suggesting the possibility to develop a vaccine using a single component of Lu. longipalpis saliva to generate protection against different species of Leishmania, even those transmitted by a different vector.